PENGEMBANGAN INSTRUMEN TES PILIHAN GANDA BERBASIS HOTS TEKS PUISI KELAS VIII - Sari Agung Tamba; Siti Samhati; Iing Sunarti (FKIP Universitas Lampung, 2022)
The problem in this research is how to develop multiple choice test instruments based on higher order thinking skills in learning poetry texts for class VIII. The purpose of this study was to make a multiple choice test instrument product based on higher order thinking skills in learning poetry texts for class VIII. This research uses research and development (rnd). The results showed the creation of a multiple-choice test instrument product based on higher order thinking skills that had been validated. The validation was carried out by lecturers and experts/practitioners to test the feasibility of the product. The results of the validation of the practitioner or peer test and the expert or expert test that has been carried out using an instrument in the form of a questionnaire. The value obtained from the practitioner or colleague is 3.72 (good) and the value obtained from the expert or expert is 3.6 (good) Masalah dalam penelitian ini adalah bagaimanakah pengembangan instrumen tes pilihan ganda berbasis higher order thinking skills pada pembelajaran teks puisi kelas VIII. Tujuan penelitian ini untuk membuat produk instrumen tes pilihan ganda berbasis higher order thinking skills pada pembelajaran teks puisi kelas VIII. Penelitian ini menggunakan research and development (rnd). Hasil penelitian menunjukkan terciptanya produk instrumen tes pilihan ganda berbasis higher order thinking skills yang sudah divalidasi.Validasi dilakukan oleh dosen dan ahli/praktisi untuk menguji kelayakan produk. Hasil validasi uji praktisi atau teman sejawat dan uji ahli atau pakar yang telah dilakukan dengan menggunakan instrument berupa angket. Nilai yang diperoleh dari praktisi atau teman sejawat adalah 3.72 (layak) dan nilai yang diperoleh dari ahli atau pakar adalah 3.6 (layak).Keywords: development, HOTS, poetry texts, question instruments